(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation:This article explores the formation of plurals in English and Uzbek languages. It highlights the main differences between the two languages in terms of pluralization rules. English primarily uses the suffixes "-s" and "-es" to form plurals, while Uzbek employs a variety of suffixes depending on the noun's phonetic structure and grammatical class. The annotation briefly touches upon the irregularities found in English plurals and emphasizes Uzbek's regular pluralization pattern. This provides a concise overview of the topic and serves as a starting point for further investigation into the plural forms in these languages.